PEMANFAATAN NIRA LONTAR SEBAGAI BAHAN PAKAN SUMBER ENERGI TAMBAHAN BAGI TERNAK BABI DAN PERBANDINGANNYA UNTUK MEMPRODUKSI GULA - Antonius Jehemat; Usaha Ginting Moenthe; Nathan Katipana (Partner, 2010)
Using of Palm Juice as Additional Energy Feedstuff of Pigs with the Comparison as Basic Material for Sugar Production. Energy resource feedstuff is high portion on pig ration. Generally, prime resource of it is cereals. Cereals used also as food and even as bio-fuel. In contradiction, production of cereals show the low trend caused the global warming and constriction of production area. As result, its price would be high and losing of breeder’s income. On the other hand there is local potential matter would be used as additive feed to extrude using of cereals. Either one is juice of palm (Borassus flabillifer) that generally found in dry region area such as East Nusa Tenggara.Now days, palm juice is used only as fresh-drink or basic material of palm sugar. Chemically, palm juice high content of soluble carbohydrate, especially sucrose, and total of metabolism energy about 3557 Kcal-kg DM. Any research reported that palm juice as additional feed able to support the growth of pig with average daily gain about 384,815 g/day. However, how much is economic value when used as additional feed of pig, especially on comparison, when used for sugar production, have not been explored.Key words: palm juice, energy feed, pigs, sugar production, and economic value.